Molecular and Functional Effects of a Splice Site Mutation in the MYL2 Gene Associated with Cardioskeletal Myopathy and Early Cardiac Death in Infants - Zhou, Zhiqun; Huang, Wenrui; Liang, Jingsheng; Szczesna-Cordary, Danuta (Frontiers in Physiology, 2016)
The homozygous appearance of the intronic mutation (IVS6-1) in the MYL2 gene encoding for myosin ventricular/slow-twitch skeletal regulatory light chain (RLC) was recently linked to the development of slow skeletal muscle fiber type I hypotrophy and early cardiac death. The IVS6-1 (c403-1G>C) mutation resulted from a cryptic splice site in MYL2 causing a frameshift and replacement of the last 32 codons by 19 different amino acids in the RLC mutant protein. Infants who were IVS6-1+/+-positive died between 4 and 6 months of age due to cardiomyopathy and heart failure. In this report we have investigated the molecular mechanism and functional consequences associated with the IVS6-1 mutation using recombinant human cardiac IVS6-1 and wild-type (WT) RLC proteins. Recombinant proteins were reconstituted into RLC-depleted porcine cardiac muscle preparations and subjected to enzymatic and functional assays. IVS6-1-RLC showed decreased binding to the myosin heavy chain (MHC) compared with WT, and IVS6-1-reconstituted myosin displayed reduced binding to actin in rigor. The IVS6-1 myosin demonstrated a significantly lower Vmax of the actin-activated myosin ATPase activity compared with WT. In stopped-flow experiments, IVS6-1 myosin showed slower kinetics of the ATP induced dissociation of the acto-myosin complex and a significantly reduced slope of the kobs-[MgATP] relationship compared to WT. In skinned porcine cardiac muscles, RLC-depleted and IVS6-1 reconstituted muscle strips displayed a significant decrease in maximal contractile force and a significantly increased Ca2+ sensitivity, both hallmarks of hypertrophic cardiomyopathy-associated mutations in MYL2. Our results showed that the amino-acid changes in IVS6-1 were sufficient to impose significant conformational alterations in the RLC protein and trigger a series of abnormal protein-protein interactions in the cardiac muscle sarcomere. Notably, the mutation disrupted the RLC-MHC interaction and the steady-state and kinetics of the acto-myosin interaction. Specifically, slower myosin cross-bridge turnover rates and slower second-order MgATP binding rates of acto-myosin interactions were observed in IVS6-1 vs. WT reconstituted cardiac preparations. Our in vitro results suggest that when placed in vivo, IVS6-1 may lead to cardiomyopathy and early death of homozygous infants by severely compromising the ability of myosin to develop contractile force and maintain normal systolic and diastolic cardiac function.